2002
DOI: 10.2343/geochemj.36.409
|View full text |Cite
|
Sign up to set email alerts
|

An alternative explanation for the distribution of highly siderophile elements in the Earth.

Abstract: The presence of highly siderophile elements (Ru, Rh, Pd, Re, Os, Ir, Pt, and Au) in the mantle has been a long standing enigma in the Earth sciences. Highly siderophile elements exhibit extremely low silicate/ metal partition coefficients and so should have partitioned into the core, leaving the mantle depleted and fractionated compared with precursor material. Late accretion of undifferentiated material after completion of core formation may have overprinted the residue inherited from metal-silicate equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Core formation resulted in a fractionated noble metal pattern in the residual mantle. If a late carbonaceous veneer was mixed with this fractionated residue, then the osmium signature of the mantle is reconciliable with a carbonaceous late veneer [ Dauphas et al , 2002a]. Note however that our conclusions do not rely heavily on this assumption.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Core formation resulted in a fractionated noble metal pattern in the residual mantle. If a late carbonaceous veneer was mixed with this fractionated residue, then the osmium signature of the mantle is reconciliable with a carbonaceous late veneer [ Dauphas et al , 2002a]. Note however that our conclusions do not rely heavily on this assumption.…”
Section: Introductionmentioning
confidence: 93%
“…We focus our discussion on osmium because its geochemistry is better known than that of other noble metals (Table 1). It has recently been suggested on the basis of the osmium isotopic composition of the mantle that there might be a concentration contrast for noble metals between the deep and the shallow mantle, the upper mantle being a factor of 3 ± 2 richer than the lower mantle [ Dauphas et al , 2002]. The osmium concentration of the upper mantle is estimated to be 0.018 × 10 −9 mol.g −1 [ McDonough and Sun , 1995], hence the osmium concentration of the deep mantle should be approximately 0.006 × 10 −9 mol.g −1 and there should be 3 − 7 × 10 16 mol of osmium in the whole mantle.…”
Section: Noble Metalsmentioning
confidence: 99%
“…First the PUM may not represent the bulk silicate Earth (BSE) (Dauphas et al, 2002). Second, given the materials from which the PUM estimate has been derived (i.e., Proterozoic to Phanerozoic mantle xenoliths and massifs), it is at least possible that this estimate includes recycled components such as radiogenic subducted slabs mixed back to the mantle via convection (Walker et al, 2002a) and/or pyroxenitic components (Allègre and Turcotte, 1986;Meibom et al, , 2004.…”
Section: Origin Of the Earth's Water And The Late Veneer(s)mentioning
confidence: 99%
“…It is thus estimated that approximately 87% of the molybdenum inventory of the upper mantle was left by core extraction and that 13% was delivered by the late veneer. Based on the osmium isotopic composition of the mantle, it was recently suggested that the late veneer was not completely homogenized in the whole mantle, its contribution being a factor of 3 or −1 higher in the upper mantle than in the lower mantle [ Dauphas et al , 2002c]. In such a case, the contribution of the residual mantle and the late veneer in the deep mantle would be 95% and 5%, respectively.…”
Section: Isotope Heterogeneity Of the Earth?mentioning
confidence: 99%